(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Cherry tomatoes are taste-bud delight, delicious and nutritious food that becomes more nourishing, healthy and appealing to consumers when produced under organic farming. The experiment was conducted at the Horticulture Farm and Postgraduate Laboratory of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh during the period from September 2019 to March 2020 to assess the effects of variety and organic manures on growth, yield and quality of cherry tomato. It was plotted in Randomized Complete Block Design with three replications. The treatments were in a factorial arrangement of 2 × 8, with 2 varieties of cherry tomato viz. V1: Binatomato-10 and V2: BARI Tomato-11 (Jhumka) and 8 different organic manures viz. T0: Control, T1: Cow dung @ 3 kg/m2, T2: Mustard oil cake (MOC) @ 0.6 kg/m2, T3: Poultry manure@ 3 kg/m2, T4: Cow dung + MOC @ (3+0.6) kg/m2, T5: Cow dung + Poultry manure @ (3+3) kg/m2, T6: MOC + Poultry manure @ (0.6+3) kg/m2, T7: Cow dung + MOC + Poultry Manure @ (3+0.6+3) kg/m2. All the parameters under study showed significant variation between cherry tomato varieties and organic manures. Binatomato-10 revealed the highest growth, yield and quality characters except plant height and number of leaves per plant compared to BARI Tomato-11 (Jhumka). Combined application of cowdung + MOC + poultry manure ensued the greatest growth, yield and quality characters in comparison with the other treatments. BARI Tomato-11 (Jhumka) accompanying the combined application of cowdung + MOC + poultry manure (V2T7) gave the highest plant height (127.75 cm) and number of leaves per plant (51.25). Binatomato-10 together with combined application of cowdung + MOC + poultry manure (V1T7) produced the highest number of fruits per plant (502.33), individual fruit weight (12.50 g), fruit length (4.23 cm) and breadth (3.22 cm), yield (89.07 t/ha), and total soluble solids (TSS) content (10.40%) while the lowest number of fruits per plant (43.55) and individual fruit weight (6.23 g), fruit length (2.10 cm) and breadth (1.79 cm), yield (8.23 t/ha) and TSS content (4.80%) was found in BARI Tomato 11 (Jhumka) with control treatment (V2T0). Therefore, Binatomato-10 together with combined application of cowdung + MOC + poultry manure was found to be better in respect of growth, yield and quality of cherry tomato. J Bangladesh Agril Univ 18(4): 982–992, 2020 https://doi.org/10.5455/JBAU.137032